ANALISIS LOCATION QUOTIENT SEKTOR DAN SUBSEKTOR PERTANIAN PADA KECAMATAN DI KABUPATEN PURWOREJO The Analysis of Location Quotient on Sector and Subsector of Agriculture among the Sub Districts in Purworejo Regency - Istiko Agus Wicaksono (Universitas Wahid Hasyim, 2011)
The objectives of this research are to find out about: (1) the identification of the agricultural basis sector and subsector among some sub districts in Purworejo regency; (2) the changes of the specialization/ the sector and subsector of agricultural base among some sub districts in Purworejo regency. This research uses a descriptive analytical method. The data used is some data from Gross Regional Domestic Product (PDRB in Indonesia) in the level of sub districts and also regency in Purworejo around the year 2000 – 2009 based on the fixed price in the year 2000. The result of this research shows that agriculture is the basic sector of 12 sub districts (75.00%); the crops subsector is the basic subsector in 10 sub districts (62.00%); the plantation crops subsector is the basic subsector in 9 sub districts (56.25%); the livestock sector is the basic subsector in 6 districts ( 37.50%); the forestry sector is the basic subsector in 7 sub districts (43.75%); and fisheries sector is the basic subsector in 5 sub districts (31.25%). Agricultural sector with the LQ trend falls in 6 sub districts (37.50%), the crops subsector with the LQ trend falls in 6 sub districts (37.50%); the plantation crops subsector with the LQ trend falls in 8 sub districts (50.00%); the livestock subsector with the LQ trend falls in 9 sub districts (56.25%); the forestry subsector with the LQ trend falls in 10 sub districts (62.50%); and the fisheries subsector with the LQ trend falls in 7 sub districts (43.75%). Based on the analysis of DLQ, agricultural sector can still be expected to be the basic sector in the future among 10 sub districts (62.50%), the crops subsector is in 8 sub districts (50.00%), the plantation crops and livestock subsectors are in 7 sub districts (43.75%), the forestry subsector is in 3 sub districts (18.75%), and the fisheries subsector is in 5 sub districts (31.25%). A combined analysis of LQ, DLQ and the LQ trend shows that the agriculture is still the basic sector of 10 sub districts in the future (62.50%), the crops subsector is in 8 sub districts (50.00%), the plantation crops subsector is in 7 sub districts (43.75%), the livestock subsector is in 8 sub districts (50.00%), the forestry subsector is in 3 sub districts (18.75%), and the fisheries subsector is in 5 sub districts (31.25%). Keywords: Sector and Subsector of Agriculture, Trend, Specialization Changes